2016
DOI: 10.1111/gtc.12375
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the HIV transcriptional activator complex in live cells by image‐based protein–protein interaction analysis

Abstract: The virus-encoded Tat protein is essential for HIV transcription in infected cells. The interaction of Tat with the cellular transcription elongation factor P-TEFb (positive transcriptional elongation factor b) containing cyclin T1 (CycT1) and cyclin-dependent kinase 9 (CDK9) is critical for its activity. In this study, we use the Fluoppi (fluorescent-based technology detecting protein-protein interaction) system, which enables the quantification of interactions between biomolecules, such as proteins, in live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…S1 Table summarizes the molecular details of the hydrogen bonding and hydrophobic interactions between CycT1 and CDK9 induced by Tat binding. Consistent with this finding from the MD simulation, we have previously reported that Tat induces increased binding affinity between CycT1 and CDK9 using image-based protein-protein interaction analysis in live cells [ 52 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…S1 Table summarizes the molecular details of the hydrogen bonding and hydrophobic interactions between CycT1 and CDK9 induced by Tat binding. Consistent with this finding from the MD simulation, we have previously reported that Tat induces increased binding affinity between CycT1 and CDK9 using image-based protein-protein interaction analysis in live cells [ 52 ].…”
Section: Resultssupporting
confidence: 84%
“…In order to clarify the structural arrangement of the Tat/P-TEFb complex, the phosphorylated Thr186 in CDK9 within the 3MI9 model was computationally substituted with an unphosphorylated Thr. The Tat sequence in the PDB data (3MI9) was substituted to match the Tat sequence used in our laboratory [ 25 , 26 , 52 ]: the substituted residues include R7N, K29R, T23N, Q35Y, V36A, I39T, T40R, and A42G (the activities of these Tat molecules are considered nearly identical). Missing side chains, loops, tails, and mutations were built using the homology modeling module in MOE ver.20140901 (Chemical Computing Group Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescent protein tags in this droplet are detected as fluorescent puncta in a reversible manner. Although the Fluoppi system is useful for detecting PPIs in living cells 24 26 , it was recently extended to allow visualization of protein homodimerization by development of a single fusion construct containing PB1 and mAG1 (homoFluoppi) that is fused to a protein of interest 23 .…”
Section: Introductionmentioning
confidence: 99%
“…We termed this method Fluoppi for Fluo rescent ppi -visualization. Fluoppi was previously employed as a general method for PPI detection242526 before its operational principle was understood or studied.…”
Section: Resultsmentioning
confidence: 99%